Analysis of differences smoking status with perianestesis oxygen desaturation to patients’ general anesthesia and regional anesthesia in the Operating Theatre Lubuk Basung Hospital - Martin, weddy; Suandika, Made; Firdaus, Eza Kemal (Riset Informasi Kesehatan, 2024)
Background: The rising prevalence of tobacco use in Indonesia over the past decade has prompted concerns about the potential health risks, particularly in the context of surgical procedures involving anesthesia. This study aimed to examine the association between smoking status and the incidence of peri anesthesia oxygen desaturation in patients undergoing general and regional anesthesia. This assessment is becoming increasingly crucial as active smokers may be at an elevated risk of oxygen desaturation, a significant complication that can occur during the administration of anesthesia, both general and regional. Method: This research is descriptive and analytic with a cross-sectional design and a total sampling of 108 respondents. The data were collected through observation of the oxygen desaturation occurring during the initial 15 minutes of anesthesia. Results: The results showed a statistically significant difference in oxygen desaturation between active and passive smokers, with a p-value of 0.000. Conclusion: Most of the respondents 56 people (51.9%) had passive smoking status and 52 respondents (48.1%) with active smoking status. The mean peri anesthesia oxygen saturation in general anesthesia and regional anesthesia patients is 90.00 with a minimum value of 91.00 and a maximum value of 100.00, with a standard deviation of 2.54309.